Thermodynamic Cards of Classic NADH Models and Their Related Photoexcited States Releasing Hydrides in Nine Elementary Steps and Their Applications - Bao-Chen Qian; Xiao-Qing Zhu; Guang-Bin Shen (Molecules)
Thermodynamic cards of three classic NADH models (XH), namely 1-benzyl-1,4-dihydronicotinamide (BNAH), Hantzsch ester (HEH), and 10-methyl-9,10-dihydroacridine (AcrH), as well as their photoexcited states (XH*: BNAH*, HEH*, AcrH*) releasing hydrides in nine elementary steps in acetonitrile are established. According to these thermodynamic cards, the thermodynamic reducing abilities of XH* are remarkably enhanced upon photoexcitation, rendering them thermodynamically highly potent electron, hydrogen atom, and hydride donors. The application of these thermodynamic cards to imine reduction is demonstrated in detail, revealing that photoexcitation enables XH* to act as better hydride donors, transforming the hydride transfer process from thermodynamically unfeasible to feasible. Most intriguingly, AcrH* is identified as the most thermodynamically favorable electron, hydride, and hydrogen atom donor among the three classic NADH models and their photoexcited states. The exceptional thermodynamic properties of XH* in hydride release inspire further investigation into the excited wavelengths, excited potentials, and excited state stabilities of more organic hydrides, as well as the discovery of novel and highly effective photoexcited organic hydride reductants.